2018
DOI: 10.1002/jia2.25091
|View full text |Cite
|
Sign up to set email alerts
|

Multiple strategies to identify HIV‐positive black men who have sex with men and transgender women in New York City: a cross‐sectional analysis of recruitment results

Abstract: IntroductionBlack men who have sex with men and transgender women are at high risk for HIV infection, but are more likely to be unaware of their infection or not in care for diagnosed HIV compared to other races. Respondent driven sampling has been advanced as a method to reach stigmatized and hidden populations for HIV testing. We compared strategies to recruit black, substance‐using men who have sex with men and transgender women to identify newly diagnosed HIV infection, or those previously diagnosed but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 77 publications
(105 reference statements)
4
8
0
Order By: Relevance
“…from fear that their sexual identities and activities could be exposed as a result of stigma from their loved ones, including family members, friends, and partners. [24][25][26] This parallels our findings regarding the strong relationship between deaf GBQ male respondents' level of PrEP knowledge and being accepted by close family and friends. Within this context, deaf GBQ men who are able to be open, maintain close relationships with loved ones, and be accepted by loved ones are more likely to be able to interact with their communities to gain stronger PrEP knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…from fear that their sexual identities and activities could be exposed as a result of stigma from their loved ones, including family members, friends, and partners. [24][25][26] This parallels our findings regarding the strong relationship between deaf GBQ male respondents' level of PrEP knowledge and being accepted by close family and friends. Within this context, deaf GBQ men who are able to be open, maintain close relationships with loved ones, and be accepted by loved ones are more likely to be able to interact with their communities to gain stronger PrEP knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…Analyses were performed using SAS 9.4 (SAS Institute, Inc. Cary, North Carolina, USA). Consistent with prior studies that compared the effectiveness of VBS and RDS for identifying undiagnosed HIV [23‐26], we did not apply VBS or RDS sampling weights in our analyses. Since our goal was not to obtain population estimates, but instead to directly compare participants recruited via each method, data needed to construct VBS sampling weights were not collected.…”
Section: Methodsmentioning
confidence: 94%
“…No difference in the proportion of those newly diagnosed with HIV following PCT, VBS or RDS recruitment was observed in a Washington DC study [23], whereas a New York City study found that PCT and RDS were equivalent but more effective than VBS [24], which differs from a Baltimore study where VBS was more effective than both PCT and RDS [25]. In another New York City study, RDS was less effective at identifying newly or previously diagnosed HIV than VBS and online recruitment where those recruited also recruited peers [26]. Within these studies, the relative effectiveness of the methods compared was attributed to the varying subgroups of MSM and TW they each reached, which may reflect contextual factors that affect the extent to which they engage different subgroups across diverse settings [27‐29].…”
Section: Introductionmentioning
confidence: 99%
“…Seeking advice from community stakeholders about language and images that will work, while complying with restrictions set by the recruitment website, is an effective strategy that can prevent oversampling and paying for large numbers of ineligible ad clicks. Advice from community advisory boards in past HIV research studies have included suggestions about advertising images/language and the social media platforms best suited for recruiting online (Franks et al, 2018;Raymond et al, 2010;Yuan, Bare, Johnson, & Saberi, 2014). There is also need for empirical research on the opinions of participants from target populations about online recruitment for HIV research specifically.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid growth of online advertising opportunities over the past twenty years, including sponsored searches (Fain & Pedersen, 2006), contextual ads (Martín-Santana & Beerli-Palacio, 2012), and behavioral advertising (Ur, Leon, Cranor, Shay, & Wang, 2012), has been accompanied by a parallel increase in the use of online paid posts for research recruitment (Gelinas, Pierce, & Cohen, 2017). Online recruitment has been especially effective for the research recruitment targeting socially stigmatized and difficult to locate diverse samples of "hidden populations" for HIV epidemiological, prevention and intervention research (Bowen, Williams, & Horvath, 2004;Chiasson et al, 2006;Du Bois, Johnson, & Mustanski, 2012;Franks et al, 2018;B. S. Mustanski, 2001;Sanchez et al, 2018;Saxton, Dickson, & Hughes, 2013;Simon Rosser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%